Dolutegravir twice-daily dosing in children with HIV-associated tuberculosis: a pharmacokinetic and safety study within the open-label, multicentre, randomised, non-inferiority ODYSSEY trial. Issue 9 (September 2022) - Turkova, Anna; Waalewijn, Hylke; Chan, Man K; Bollen, Pauline D J; Bwakura-Dangarembizi, Mutsa F; Kekitiinwa, Adeodata R; Cotton, Mark F; Lugemwa, Abbas; Variava, Ebrahim; Ahimbisibwe, Grace Miriam; Srirompotong, Ussanee; Mumbiro, Vivian; et al.
Summary: Background: Children with HIV-associated tuberculosis (TB) have few antiretroviral therapy (ART) options. We aimed to evaluate the safety and pharmacokinetics of dolutegravir twice-daily dosing in children receiving rifampicin for HIV-associated TB. Methods: We nested a two-period, fixed-order pharmacokinetic substudy within the open-label, multicentre, randomised, controlled, non-inferiority ODYSSEY trial at research centres in South Africa, Uganda, and Zimbabwe. Children (aged 4 weeks to <18 years) with HIV-associated TB who were receiving rifampicin and twice-daily dolutegravir were eligible for inclusion. We did a 12-h pharmacokinetic profile on rifampicin and twice-daily dolutegravir and a 24-h profile on once-daily dolutegravir. Geometric mean ratios for trough plasma concentration (Ctrough ), area under the plasma concentration time curve from 0 h to 24 h after dosing (AUC0–24 h ), and maximum plasma concentration (Cmax ) were used to compare dolutegravir concentrations between substudy days. We assessed rifampicin Cmax on the first substudy day. All children within ODYSSEY with HIV-associated TB who received rifampicin and twice-daily dolutegravir were included in the safety analysis. We described adverse events reported from starting twice-daily dolutegravir to 30 days after returning to once-daily dolutegravir. This trial is registered with ClinicalTrials.gov (NCT02259127 ), EudraCT (2014–002632-14), and the ISRCTN registry (ISRCTN91737921). Findings: Between Sept 20, 2016, and June 28, 2021, 37 children with HIV-associated TB (median age 11·9 years [range 0·4–17·6], 19 [51%] were female and 18 [49%] were male, 36 [97%] in Africa and one [3%] in Thailand) received rifampicin with twice-daily dolutegravir and were included in the safety analysis. 20 (54%) of 37 children enrolled in the pharmacokinetic substudy, 14 of whom contributed at least one evaluable pharmacokinetic curve for dolutegravir, including 12 who had within-participant comparisons. Geometric mean ratios for rifampicin and twice-daily dolutegravir versus once-daily dolutegravir were 1·51 (90% CI 1·08–2·11) for Ctrough, 1·23 (0·99–1·53) for AUC0–24 h, and 0·94 (0·76–1·16) for Cmax . Individual dolutegravir Ctrough concentrations were higher than the 90% effective concentration (ie, 0·32 mg/L) in all children receiving rifampicin and twice-daily dolutegravir. Of 18 children with evaluable rifampicin concentrations, 15 (83%) had a Cmax of less than the optimal target concentration of 8 mg/L. Rifampicin geometric mean Cmax was 5·1 mg/L (coefficient of variation 71%). During a median follow-up of 31 weeks (IQR 30–40), 15 grade 3 or higher adverse events occurred among 11 (30%) of 37 children, ten serious adverse events occurred among eight (22%) children, including two deaths (one tuberculosis-related death, one death due to traumatic injury); no adverse events, including deaths, were considered related to dolutegravir. Interpretation: Twice-daily dolutegravir was shown to be safe and sufficient to overcome the rifampicin enzyme-inducing effect in children, and could provide a practical ART option for children with HIV-associated TB. Funding: Penta Foundation, ViiV Healthcare, UK Medical Research Council.